Post-extubation dysphagia in intensive care - a prospective observational study - Saibertová, Simona; Bolechová, Vendula; Pokorná, Andrea (Kontakt, 2025)
Purpose: Dysphagia may occur in all critically ill patients, and large-scale clinical data show that post-extubation dysphagia (PED) is commonly observed in intensive care unit (ICU) patients. The study aimed to determine how dysphagia is diagnosed after extubation, and what factors influence the incidence of dysphagia after invasive airway support in selected ICUs. Methods: A prospective observational study was conducted for five months (07/2023 to 11/ 2023), in the acute ICU and long-term ICU of the Teaching hospital in the Czech Republic. Results: Of the 101 extubated patients in the study, only 27.7% (n = 28) were examined by a physician, and PED was confirmed in 26.7% (n = 27), representing 99% of all extubated patients. Age, gender, and ICU type were not significantly related to PED occurrence. However, the type of airway management (p < 0.001), duration of mechanical ventilation (p = 0.017), and main diagnosis (p < 0.001) were significantly associated with PED occurrence. Conclusion: The study confirmed the underdiagnosis of PED in ICU patients post-extubation. Higher PED incidence was linked to tracheostomy + endotracheal cannula use, mechanical ventilation longer than 9 days, and neurological diagnoses. Training health professionals to identify PED symptoms is essential to establish uniform procedures for diagnosing and preventing PED-related complications.
Keywords: Prospective Studies; Critical Care; Ventilators, Mechanical; Humans; Airway Extubation; mechanické ventilátory; prospektivní studie; Tracheostomy; Intubation, Intratracheal; Czech Republic; Deglutition Disorders; Česká republika; poruchy polykání; extubace; umělé dýchání; Respiration, Artificial; intratracheální intubace; lidé; tracheostomie; péče o pacienty v kritickém stavu